2020
DOI: 10.21203/rs.3.rs-33814/v3
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Sedentary Behaviour Among General Practitioners: A Systematic Review

Abstract: BackgroundSedentary behaviour is when someone is awake, in a sitting, lying or reclining posture and is an independent risk factor for multiple causes of morbidity and mortality. A dose-response relationship has been demonstrated, whereby increasing sedentary time corresponds with increasing mortality rate. This study aimed to identify current levels of sedentary behaviour among General Practitioners (GPs), by examining and synthesising how sedentary behaviour has been measured in the primary care literature.M… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1
1

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 47 publications
0
2
0
Order By: Relevance
“…Sedentary behavior has a relationship with health conditions, including mental health, obesity, type 2 diabetes mellitus, cardiovascular disease, and breast, colorectal, endometrial, and ovarian cancers [36]. In addition, sedentary behavior also has a negative impact on mental health, namely anxiety disorders and depression [37], [38]. In another study, sedentary behavior can also increase the risk of insomnia and sleep disturbances [39].…”
Section: Discussionmentioning
confidence: 97%
“…Sedentary behavior has a relationship with health conditions, including mental health, obesity, type 2 diabetes mellitus, cardiovascular disease, and breast, colorectal, endometrial, and ovarian cancers [36]. In addition, sedentary behavior also has a negative impact on mental health, namely anxiety disorders and depression [37], [38]. In another study, sedentary behavior can also increase the risk of insomnia and sleep disturbances [39].…”
Section: Discussionmentioning
confidence: 97%
“…A recent systematic review, conducted by the authors, identified two previous studies reporting levels of sedentary behaviour among GPs [36]. Keohane et al examined GP trainees and GP trainers in Ireland in 2018, when 60% reported spending in excess of seven hours, 24% between four and seven hours, and 16% less than or equal to four hours sitting each day [28].…”
Section: Comparison With Existing Literaturementioning
confidence: 99%